CT genotype of 5, 10-methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism is protector factor of major depressive disorder in the Tunisian population: a case control study. Issue 1 (December 2016) - Sayadi, Mohamed; Achour, Ons; Ezzaher, Asma; Hellara, Ilham; Omezzine, Asma; Douki, Wahiba; Bousslama, Ali; Gaha, Lotfi; Najjar, Mohamed
Abstract Background Major depressive disorder (MDD) is a common psychiatric disorder with considerable mortality. Death from unnatural causes, largely suicidal or quasi-suicidal, has a particularly high risk for the functional disorders, especially depression and schizophrenia. One of the prospective risk factors for this disease is hyperhomocysteinemia and folate deficiency. The methylenetetrahydrofolate reductase (MTHFR) gene encodes for a 5-methylenetetrahydrofolate reductase involved in folate metabolism and neurotransmitter synthesis. The aim of this research is to study the association between the C677T polymorphism of MTHFR gene and depression in Tunisian population, to explore their relationship with clinical and therapeutic characteristics of this disease. And it may lead to discover a novel marker to identify a patient with a higher risk of development of depressive disorder to be. This marker can be used for better therapeutic management and prevent disease installation. Methods Our study included 208 depressive patients, 187 controls aged between 44.1 ± 13.5 and 38.9 ± 13.2 years, respectively. MTHFR gene polymorphisms were determined by PCR–RFLP (polymerase chain reaction–restriction fragment length polymorphism). Results No significant difference was detected in the distribution of the genotype frequencies of MTHFR C677T polymorphisms (χ 2  = 5.443, df = 2, p  = 0.066) between patients and controls. But when we study the risk of these genotypes, CT genotype is significantly more frequent in controls compared to patients, it may be a protection from depression (OR = 0.655, CI 95 % = 0.432–0.995, p  = 0.047, OR* = 0.638, CI 95 %* = 0.415–0.983, p * = 0.04, before and after adjustment). Women, TT Genotype can increase four times the risk to be depressive. Addictive behavior seems to be associated with CT genotype and there was no significant association between clinical and therapeutic characteristics and this polymorphism. Conclusion This paper is the first study to prove that CT genotype of MTHFR C677T polymorphism may protect from depression and TT genotype seems to be associated with women's depression. Further studies are required with other polymorphisms and biochemical factors that must be investigated to clarify the implication of MTHFR C677T polymorphism in the pathophysiology of depression.